THE ROLE OF DIGITAL FINANCE AND TECHNOLOGICAL INNOVATION IN THE GROWTH OF THE GREEN ECONOMY - Umarov Azizjon Azamjon oʻgʻli; Musabekov Sherali Nazarali oʻgʻli (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The development of green economy has become a global trend, and digital finance and technological innovation are playing an increasingly important role in promoting its growth. This article explores the application trend of digital finance and technological innovation in the development of green economy. It discusses how digital finance can provide new financing channels for green projects, and how technological innovation can improve the efficiency and effectiveness of green production and consumption. The article also analyzes the challenges and opportunities facing the development of digital finance and technological innovation in the green economy, and provides suggestions for future development. Overall, this article highlights the potential benefits of integrating digital finance and technological innovation into the development of green economy, and emphasizes the importance of promoting sustainable and inclusive economic growth.